Citrus and Peach Urban Landscapes in Limone and Montreuil - Condello, Annette (2016)
What does the tourist town of Limone on Lake Garda in Italy have in common with suburban Montreuil in France? Reinterpreting the infrastructural constructions to house fruits in these places, this paper will trace their lesser-known architectural marks through the urban landscape based upon established memories. In 19th century-Europe the citrus and peach industries reached their peak, but by the turn of the 20th century these sought-after agricultural/luxury commodities went into decline: peaches were no longer tattooed with artisanal stamps and lemons were tainted with a disease. First, this paper analyses the citrus architecture, specifically the lemon greenhouses along Lake Garda’s towns. Then, it compares them with the criss-cross spaces for peaches within walls (aka peach walls), created in suburban Montreuil, near Paris. Observing the links between these two cases, it is concerned with memory traces, argued herein as promoting functional vestiges in European urban landscapes. Referring to German landscape architect Leberecht Migge’s writings, the paper questions why such functional vestiges operated as alternative allotments in the urban landscape elsewhere in Europe. How have they provided luxurious spaces or the cleansing of entrenched spaces for those who live or work outside the city or suburb? Although the spaces within such infrastructural constructions have since declined, peach walls have subsequently been converted into public spaces as with Jean Nouvel and Michel Desvigne’s 800 kilometres ‘seam’ design (2009) near Paris. And traces of the lemon greenhouses have inspired David Chipperfield’s new private luxury houses (2015) at Lake Garda. This comparison of the remnant fruit-growing traces of Limone and Montreuil through the landscape enabled remnant spaces to become sustainable places today. Urban citrus-spaces cleanse microclimates and the conversion of peach walls provides us with beneficial changes as communal spaces.